2007
DOI: 10.1016/j.rmed.2006.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Aetiology in adult patients with bronchiectasis

Abstract: Full investigation of problematic cases should occur in a specialist centre because results affect management in a third of cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
181
2
17

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 263 publications
(222 citation statements)
references
References 28 publications
(52 reference statements)
9
181
2
17
Order By: Relevance
“…Previous studies show that 26%-53% of cases of bronchiectasis have no known cause [65,66]. Chronic airway inflammation is supposed to be the primary cause of bronchiectasis, as observed in a condition that involves the airways, such as recurrent pulmonary infections, and autoimmune disease.…”
Section: Bronchiectasismentioning
confidence: 99%
“…Previous studies show that 26%-53% of cases of bronchiectasis have no known cause [65,66]. Chronic airway inflammation is supposed to be the primary cause of bronchiectasis, as observed in a condition that involves the airways, such as recurrent pulmonary infections, and autoimmune disease.…”
Section: Bronchiectasismentioning
confidence: 99%
“…While idiopathic cases are most common, several risk factors and etiologies for the development of bronchiectasis were identified in previous studies on symptomatic bronchiectasis (Nicotra et al 1995;Pasteur et al 2000;Shoemark et al 2007): postinfectious complications, mucociliary clearance defects associated with genetic diseases, immune deficiency, and chronic inflammatory conditions such as rheumatoid arthritis and inflammatory bowel disease. Of these, infectious diseases, including pulmonary TB, pertussis, measles, and nontuberculous Mycobacterial infection, were most frequently associated with the risk of developing bronchiectaisis.…”
Section: Respiratory Symptoms % (N)mentioning
confidence: 99%
“…(12) Recent studies that attempted to determine the etiology of bronchiectasis in patients with cough, expectoration, and tomographic findings suggestive of bronchiectasis showed that the idiopathic form of the disease occurred in 26-53% of the patients. (13,14) Bronchiectasis caused by viral infections in childhood, humoral immunodeficiency, allergic bronchopulmonary aspergillosis, CF, and aspiration were the diseases most frequently diagnosed after the systematic analysis of these patients. The determination of the underlying disease requires considerable diagnostic effort and, in most cases, does not improve the prognosis or does not alter the clinical condition of the patients.…”
Section: Discussionmentioning
confidence: 99%
“…The determination of the underlying disease requires considerable diagnostic effort and, in most cases, does not improve the prognosis or does not alter the clinical condition of the patients. According to one group of authors, (14) although the etiologic diagnosis was made in as many as 74% of the cases referred to a tertiary facility for the treatment of respiratory diseases, the treatment was changed in only 36% of the cases. However, the identification of allergic bronchopulmonary aspergillosis, rheumatoid arthritis, common variable immunodeficiency, aspiration pneumonia, and alpha-1 antitrypsin deficiency allows the initiation of specific treatment and behavioral counseling that can change the course of the disease.…”
Section: Discussionmentioning
confidence: 99%